Do Language Policies in South Africa Symbolically Erase Multilingualism? - (:unkn) unknown (My University, 2007)
This essay examines the relationship of national language policies to ground-level language practices. The language repertoires and actual speech behaviours of people living in a township in North West Province are contrasted with the language policies in their schools. To the extent that the official language policies do not reflect the lived realities of people in this region, I ask what assumptions about language, ethnicity and nationhood underpin these policies and enable people to "make sense" of the gap between language policy and language practice. I employ the semiotic concept of "erasure" to theorize the ideological process that takes place when certain dominant ideas, through their implicit assumptions and discursive force, render invisible particular social phenomena, including speech behaviour.
Keywords: African Research